The landscape of European policies in the power sector: first-mover advantages - Kristina Govorukha; Philip Mayer; Dirk Rübbelke (Mitigation and Adaptation Strategies for Global Change, 2023)
In order to achieve the commonly agreed emission reduction target, the European Commission called upon the member states to submit National Energy and Climate Plans to ensure increased transparency for the respective national targets and strategies. An analysis of these plans shows that some member states have declared ambitious emission reductions targets, as well as technology-specific phaseout policies in the power sector. A transformation to a climate-friendly system requires considerable investment, the question arises if there are benefits to be in the vanguard. We find that countries may have an incentive to outperform in the development of a low-carbon electricity system.
Keywords: 330; Electricity; Utilities; Thermal generation; Unilateral action; Climate policy; C6 Mathematical methods; Programming models; Mathematical and simulation modeling; Q4 Electricity; Energy; Energy Utilities; Gas; Hydrocarbons